Clifford Goes to Dog School - Bridwell, Norman (New York, 2002)
Auntie, who is a dog trainer, thinks Clifford needs to learn obedience, but to Emily Elizabeth the big red dog is perfect already.
Keywords: Fiction; Dogs; Training; Fiction; Dogs; Fiction; Dogs; Fiction; Dogs; Training